KEY SUCCES FACTORS STRUKTUR MODAL PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bambang Jatmiko; Putro Juwono Siswantoro (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
The purpose of this research is want to know the effect of business risk factors, profitability, asset growth, liquidity, and sales growth to influence the capital structure of the food and beverage company in Indonesia Stock Exchange for the years 2006 to 2009 The Sample which is used in this Research 10 food and beverage companies in the consumer goods sector industry from 2006 to 2009. The method that used is purposive sampling. It is a sampling method that takes an object with certain criteria. The Result of data analysis partially showed that there was effect of business risk, profitability, assets growth, liquidity and sales growth on the capital structure with a significant level of each 0.000, 0.002, 0.005, 0.000, 0.020. Then the result of simultant analysis data showed that variable business risk, profitability, asset growth, liquidity and sales growth has affected to capital structure with a significant level of 0.000 and the greatest effect 64.9% and the remaining 35.1% described other variables.Keywords: capital structure, business risk, profitability, asset growth, liquidity and sales growth.